The Effect of Tax Knowledge, Tax Rates, and Tax Sanctions on E-Commerce Taxpayer Compliance in Indonesia - Radea Respati Paramudhita; Ivan Gumilar Sambas Putra (International Journal of Economics, Business and Innovation Research, 2026)
The rapid expansion of e-commerce has transformed business activities and posed new challenges for tax compliance, particularly among individual digital entrepreneurs operating in platform-based markets. This study aims to examine the effects of tax socialization, tax knowledge, taxpayer awareness, and tax sanctions on e-commerce taxpayer compliance by employing a quantitative explanatory approach. Primary data were collected through structured questionnaires from 80 individual e-commerce entrepreneurs operating on the Shopee marketplace in Bandung City, Indonesia, and analyzed using Structural Equation Modeling based on Partial Least Squares (SEM-PLS) with SmartPLS 3.0. The results indicate that tax knowledge and taxpayer awareness have a positive and significant effect on taxpayer compliance, whereas tax socialization and tax sanctions do not significantly influence compliance behavior. These findings suggest that compliance in the digital economy is primarily driven by internal cognitive understanding and normative awareness rather than by external enforcement-oriented mechanisms. This study contributes to the accounting and taxation literature by reinforcing the relevance of behavioral perspectives, particularly compliance theory and the Theory of Planned Behavior, in explaining taxpayer behavior in digital business environments and provides practical implications for tax authorities to prioritize education- and awareness-based strategies supported by digital engagement to enhance voluntary compliance among e-commerce entrepreneurs.